Systemic Lupus Concealed in the Shadow of a Primary Membranous Nephropathy Diagnosis - Castro,Pedro Almiro e (2023)
ABSTRACT A 43-year-old male patient followed for 27 years in a Nephrology consultation with negative autoimmune diagnostic workup and a histologically proven membranous nephropathy (MN), interpreted as a primary MN. During the follow-up he had multiple relapses, requiring continuous immunosuppression. Eventually, end-stage renal disease developed and the patient started hemodialysis (HD) in January 2018. Soon after initiating HD, he was admitted to the ward due to persistent fever of unknown origin, refractory to antipyretic and antibiotic therapy, but responsive to prednisolone (40 mg/day). Again, the diagnostic workup was negative and the patient was discharged with a corticosteroid taper over 16 weeks. In a posterior admission, after prednisolone suspension, the patient presented to the emergency room with persistente fever, involuntary weight loss, pruriginous macular rash and inflammatory joint pain. As the anti-nuclear antibody and anti-dsDNA came up positive and there was complement consumption, a diagnosis of a systemic lupus flare was established. His stay was complicated by sudden respiratory distress associated with hemoptysis and hemoglobin drop, with a confirmed diffuse alveolar hemorrhage. Daily plasma Exchange and intensive immunosuppression was necessary and the patient evolved into complete clinical remission with partial serological response. Usually, patients with systemic lupus erythematosus (SLE) develop clinical and serological remission upon initiating HD, reducing the number of flares and need for medication. This case depicts a lupus flare after starting HD, on a previously serologically negative patient, complicated with a rare type of lung parenchyma involvement, which is associated with a high mortality and required intensive immunosuppression for disease control. One can speculate whether or not the initial glomerulopathy was the first manifestation of SLE, previously controlled due to the continuous use of immunosuppression.